Molecular Sensors of Blood Flow in Endothelial Cells. Issue 9 (September 2017) - Baratchi, Sara; Khoshmanesh, Khashayar; Woodman, Owen L.; Potocnik, Simon; Peter, Karlheinz; McIntyre, Peter
Abstract : Mechanical stress from blood flow has a significant effect on endothelial physiology, with a key role in initiating vasoregulatory signals. Disturbances in blood flow, such as in regions of disease-associated stenosis, arterial branch points, and sharp turns, can induce proatherogenic phenotypes in endothelial cells. The disruption of vascular homeostasis as a result of endothelial dysfunction may contribute to early and late stages of atherosclerosis, the underlying cause of coronary artery disease. In-depth knowledge of the mechanobiology of endothelial cells is essential to identifying mechanosensory complexes involved in the pathogenesis of atherosclerosis. In this review, we describe different blood flow patterns and summarize current knowledge on mechanosensory molecules regulating endothelial vasoregulatory functions, with clinical implications. Such information may help in the search for novel therapeutic approaches. Trends: Molecular sensors of blood flow enable the translation of mechanical stimuli associated with blood flow into molecular responses that in turn regulate the tension in blood vessels. Identifying such molecules and understanding their function may provide a starting point for the treatment of different cardiovascular pathologies. Atherosclerosis is closely associated with remodeling of the extracellular matrix via the accumulation of fibronectin in the laminin-collagen basal membrane. Inflammation associated with atherosclerosis is regulated, at least in part, via the interaction of α5 integrins with fibronectin. Piezo1 is a mechanosensitive ion channel that is proposed to gate directly in response to shear stress. This channel is required for flow-induced ATP release and activation of downstream signaling pathways in endothelial cells and red blood cells. Shear stress controls exocytosis and interaction of mechanoreceptors, such as transient receptor potential (TRP)V4, cadherins, and integrins, on the cell membrane. These relocations and interactions have important roles in maintaining the physiological functions of blood flow on exposed cells. The flow-sensing pathway platelet endothelial cell adhesion molecule-1 (PECAM-1)/VE-cadherin/vascular endothelial growth factor receptors (VEGRs), which controls the endothelial alignment to the direction of flow, can regulate atherogenesis and could be targeted to prevent and/or alter the progression of atherosclerosis.